2017
DOI: 10.1002/adem.201700703
|View full text |Cite
|
Sign up to set email alerts
|

Using Post‐Deformation Annealing to Optimize the Properties of a ZK60 Magnesium Alloy Processed by High‐Pressure Torsion

Abstract: A ZK60 magnesium alloy with an initial grain size of %10 mm is processed by high-pressure torsion (HPT) through 5 revolutions under a constant compressive pressure of 2.0 GPa with a rotation speed of 1 rpm. An average grain size of %700 nm is achieved after HPT with a high fraction of highangle grain boundaries. Tensile experiments at room temperature show poor ductility. However, a combination of reasonable ductility and good strength is achieved with post-HPT annealing by subjecting samples to high temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Also, a short annealing after HPT processing may increase the ductility. For example, an increase in strength and a remarkably uniform elongation of 20.5% was reported in a ZKX600 alloy processed by HPT and subjected to a 1 min annealing treatment at 300 °C and an increase in elongation was reported also in a ZK60 alloy processed by HPT and annealed for 20 min at 200 °C …”
Section: Mechanical Propertiesmentioning
confidence: 93%
“…Also, a short annealing after HPT processing may increase the ductility. For example, an increase in strength and a remarkably uniform elongation of 20.5% was reported in a ZKX600 alloy processed by HPT and subjected to a 1 min annealing treatment at 300 °C and an increase in elongation was reported also in a ZK60 alloy processed by HPT and annealed for 20 min at 200 °C …”
Section: Mechanical Propertiesmentioning
confidence: 93%
“…Earlier investigations of authors on the ZK60 Mg alloy showed that HPT induced an inhomogeneous strain along the radius of samples by torsional straining and, as a result, the average grain size and the mechanical properties tended to vary along the radius of the samples but an almost homogeneous microhardness distribution with finer grain size and reasonable uniformity was attained after higher numbers of HPT turns [27][28][29]. The mechanical and thermal stability behavior of ZK60 after HPT was evaluated recently by the current authors [30,31] but it is imperative to study the electrochemical behavior of the refined ZK60 alloy. Accordingly, this research was initiated to assess the electrochemical and semiconductive oxide layer behavior of the ZK60 Mg alloy after processing through HPT with different numbers of turns and to make a direct comparison with the behavior of extruded material.…”
Section: Introductionmentioning
confidence: 94%
“…In another study, cold rolling followed by annealing of CoCrNi alloy is reported to have an ultra-fine-grained size (~750 nm) with a good combination of tensile strength (964 MPa) and strain to failure (66%) [ 20 ]. In this connection, high-pressure torsion (HPT) followed by annealing has been effectively used in conventional alloys and HEAs to improve their mechanical properties [ 21 , 22 , 23 ]. Generally, HPT is an effective process in fabricating materials with nano-grains or ultra-fine grained structure by simultaneous application of torsion and high hydrostatic pressure [ 22 ].…”
Section: Introductionmentioning
confidence: 99%